Non-Linear Analysis Of Reinforced And Pre-Stressed Concrete Beams - Hamed, Ahmed M.m. (2002)
Reinforced/pre-stressed (RC/PC) concrete is one of the most commonly used construction materials. This composite material demonstrates a highly non-linear behaviour caused by, cracking, crushing, aggregate interlock, bond slip, dowel action, shrinkage, creep, etc. Because the behaviour of reinforced/pre-stressed concrete involves so many non-linear phenomena interacting with one other, the formulation of rational analytical procedures to describe this behaviour is very difficult Since the advent of the computer, powerful methods of analysis such as the finite element method and stiffness matrix method have been implemented to study and develop analytical solutions for the non-linear phenomena. However, the success of such analysis depends on a thorough understanding and modeling of the composite material behaviour.This study describes the development of a non-linear computer code used to predict the non-liner response of reinforced/pre-stressed concrete beams that are subjected to a combined axial force and bending moment The study discusses a new simplified approach, whereby the non-linear response is captured via a series of sequentially linear steps. The finite element approach with the stiffness matrix method were used to model the beam element structure and generate its stiffness matrix. A monotonic empirical model for the concrete's stress-strain curve has been implemented to predict both ascending and descending parts of the curve. An idealized bi-linear elasto-plastic in tension and compression model has been assumed for reinforcing and pre-stressing steel.